Adaptive Statistical Iterative Reconstruction–V Versus Adaptive Statistical Iterative Reconstruction: Impact on Dose Reduction and Image Quality in Body Computed Tomography. Issue 2 (March 2018) - Gatti, Marco; Marchisio, Filippo; Fronda, Marco; Rampado, Osvaldo; Faletti, Riccardo; Bergamasco, Laura; Ropolo, Roberto; Fonio, Paolo
Abstract : Objective: The aim of this study was to evaluate the impact on dose reduction and image quality of the new iterative reconstruction technique: adaptive statistical iterative reconstruction (ASIR-V). Methods: Fifty consecutive oncologic patients acted as case controls undergoing during their follow-up a computed tomography scan both with ASIR and ASIR-V. Each study was analyzed in a double-blinded fashion by 2 radiologists. Both quantitative and qualitative analyses of image quality were conducted. Results: Computed tomography scanner radiation output was 38% (29%–45%) lower ( P < 0.0001) for the ASIR-V examinations than for the ASIR ones. The quantitative image noise was significantly lower ( P < 0.0001) for ASIR-V. Adaptive statistical iterative reconstruction–V had a higher performance for the subjective image noise ( P = 0.01 for 5 mm and P = 0.009 for 1.25 mm), the other parameters (image sharpness, diagnostic acceptability, and overall image quality) being similar ( P > 0.05). Conclusions: Adaptive statistical iterative reconstruction–V is a new iterative reconstruction technique that has the potential to provide image quality equal to or greater than ASIR, with a dose reduction around 40%.